Current directions in computer-assisted cognitive rehabilitation. - Gontkovsky ST; McDonald NB; Clark PG; Ruwe DW (NeuroRehabilitation, 2002)
Technological advances over the past decade have given rise to the development of multiple computer-assisted cognitive rehabilitation programs. While results of investigations examining the efficacy of such techniques have been mixed, a positive trend for utilization of these procedures has been demonstrated. This review provides a discussion of the progression of research in this area, from anecdotal studies to controlled empirical investigations. Methodological shortcomings are examined and directions for future research in computer-assisted cognitive rehabilitation suggested.